Ferromanganese production from the mixture of medium-grade and low-grade Indonesian manganese ore. Issue 2 (3rd April 2018) - Nurjaman, Fajar; Saputra, Hendri; Astuti, Widi; Ferdian, Deni; Suharno, Bambang
Abstract: In this present work, the ferromanganese was produced by mixing two different grades of Indonesian manganese ore. The possibility of mixing medium-grade manganese ore (27.77 Mn–4.44 Fe–14.7 Si) and low-grade manganese ore (16.39 Mn–19.22 Fe–20.23 Si) to produce ferromanganese was investigated clearly. The 30 Kg of manganese ore mixture was smelting by using sub-merged arc furnace (SAF). The composition of manganese ore mixture in percent weight to produce ferromanganese was 100–0, 75–25, 50–50, 25–75, and 0–100 for medium-grade and low-grade manganese ore, respectively. These ores were smelted together with stoichiometry cokes. Limestone was added in this smelting process to obtain 0.75 of basicity in this smelting process. The chemical composition of ferromanganese was analyzed with X-Ray Fluorescence (XRF). From the smelting process, the ferromanganese with 31.13 Mn–59.84 Fe–7.84 Si and 75.19 Mn–20.17 Fe–3.27 Si were resulted from 100% of low-grade and medium-grade manganese ore, respectively. The Mn-content in ferromanganese and the yield of ferromanganese production were decreased with the increasing of low-grade manganese ore in the mixture of low-grade and medium-grade manganese ore smelting process.